Parametric selection of hybrid parts for additive manufacturing - Michael Schöppe; Kaj Fuehrer (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The combination of additive and conventional manufacturing techniques allows the combination of the strengths of both approaches. Additive manufacturing can be concentrated on functional and complex geometries while the basic body of a part is produced conventionally leading to cost advantages and thus enables new application fields of additive manufacturing. Methodology: To identify parts suitable for a hybrid production, the application of a software evaluating part properties based on CAD data were examined. Different criteria for the selection of components are presented and tested. The methodology was qualitatively validated by an exemplary application to a library of 3D models of components using the 3D Partfinder software. Findings: By applying the presented criteria for the part selection, the software can automatically perform the necessary part comparison. It can be concluded that the complexity index allows a typologization of parts while respecting economic parameters. In particular products with a high number of variants but only small geometric deviations in volume and surface area show a high potential for hybrid production. Originality: So far, little research on hybrid additive manufacturing has been done. The paper shows the applicability of software solutions and offers typologization criteria as a general search strategy for suitable parts.
urn:nbn:de:gbv:830-882.0161996; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Advanced Manufacturing; Industry 4.0